Controversies and opportunities of two development measures for the advancement of women in Uganda: Formal education and Women entrepreneurship - Namasembe, Olga; Manzanera Ruiz, Roser (Journal of Education Culture and Society, 2021)
Aim. The aim of the research is to investigate the relationship between formal education and female entrepreneurship in Uganda. This research hopes to contribute to the literature on education and women’s entrepreneurship in this country. Methods. Data is collected from 109 women through semi structured interviews. These are participants from the agribusiness sector and own businesses ranging from market stalls, retail shops to street businesses. Through the iterative process, emerging themes are analysed and discussed. Results. The research finds that formal education programs and macroeconomic policies negatively impact formal education and female entrepreneurship. Macroeconomic policies such as privatisation and the programs of universal formal education do not incentivize students (specifically female ones) to pursue a full formal education, influencing them to leave schools early for necessity entrepreneurship to meet immediate needs. Conclusions. Even though the study indicates that a formal education demonstrates high outcomes in terms of economic growth and development, the education level attained by women entrepreneurs is insufficient to meet true entrepreneurial success. Furthermore, the macroeconomic environment adds to the challenge of successful women entrepreneurship. Originality. Various economic initiatives have been implemented in the quest for gender parity in education and women empowerment in Uganda since its independence. Statistics have demonstrated an increase in women’s education and empowerment through entrepreneurship, however, such data do not necessarily reflect economic development. The results suggest that the relationship between formal education and women entrepreneurship is more complex and nuanced than previously believed.